Retorika Syekh Abdul Efendi Ritonga dalam Ceramah - Nurlahani siregar (Universitas Islam Negeri Imam Bonjol Padang, 2019)
As the reason for this research is Sheikh Abdul Efendi Ritonga, a charismatic cleric in Parmeraan Village, Kec. North Sumatra's Dolok Padang Lawas with its gentle but firm delivery, he was also one of those who tried to make progress in Parmeran Village with the knowledge he had. His da'wah has been dozens of years. He is one of the most respected in North Padang Lawas Regency and its surroundings. The main problem in this study is how intonation, gesture and style of Sheikh Abdul Efendi Ritonga in lecturing. The objectives of this study are: (1) To find out the biography of Sheikh Abdul Efendi Ritonga, (2) To find out the intonation of Sheikh Abdul Efendi Ritonga in lecturing, (3) To know Sheikh Abdul Efendi Ritonga's gesture in lecturing, (4) To know the language style lecture. This study uses qualitative methods that are descriptive in nature, using a biographical study approach. As the source of this data is Syekh Abdul Efendi Ritonga, his family and the community in Parmeraan Village. Techniques for collecting data are observation, interviews and documentation with descriptive analysis. The results of this study are (1) the intonation he used in lecturing very clearly the emphasis on the words he uttered, he knew when to use high notes and when his tone should be lowered. (2) The body movements that are used are hand gestures, various directions, relaxed, not tense, and not anxious and this gesture is adjusted to the material situation presented. (3) The style of language he uses in delivering his lectures is to use the style of repetition, anthesis, equality and allusion with a quality language, easily understood and understood by mad'u.